2016
DOI: 10.1016/j.str.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

From Nanodiscs to Isotropic Bicelles: A Procedure for Solution Nuclear Magnetic Resonance Studies of Detergent-Sensitive Integral Membrane Proteins

Abstract: Summary Nanodiscs and isotropic bicelles are promising membrane mimetics in the field of solution NMR spectroscopy of integral membrane proteins (IMPs). Despite varied challenges to solution NMR studies of IMPs, we attribute the paucity of solution NMR structures in these environments to the inability of diverse IMPs to withstand detergent treatment during standard nanodisc and bicelle preparations. Here, we present a strategy that creates small isotropic bicelles from IMPs co-translationally embedded in large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
(66 reference statements)
2
28
0
Order By: Relevance
“…High‐resolution biophysical techniques commonly use detergent micelles to mimic a hydrophobic environment because they are easy to handle and very homogeneous in size. However, due to the artificial nature and frequent denaturing capabilities of detergents, as well as a high degree of curvature in micelles, membrane proteins and membrane‐associated peptides might not adapt their natural shape/topology, but might bend unnaturally under steric restraints 7, 30, 47. These structural artefacts can be avoided by using artificial vesicles named liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…High‐resolution biophysical techniques commonly use detergent micelles to mimic a hydrophobic environment because they are easy to handle and very homogeneous in size. However, due to the artificial nature and frequent denaturing capabilities of detergents, as well as a high degree of curvature in micelles, membrane proteins and membrane‐associated peptides might not adapt their natural shape/topology, but might bend unnaturally under steric restraints 7, 30, 47. These structural artefacts can be avoided by using artificial vesicles named liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…The optimized substrates discovered here will help us and others develop more sensitive in vitro and cell‐based assays to measure Lsp activity. Interpreting our results based on X‐ray or NMR structures of Lsp, especially Lsp from E. coli and S. pyogenes, will give us further mechanistic insights into substrate recognition of Lsp .…”
Section: Resultsmentioning
confidence: 82%
“…Previous experience with membrane proteins has shown that, using combinatorial selective labeling protocols that comprise three or four different classes of labeled amino acids, full backbone assignments may still be obtained in situations where critical 3D experiments fail. This approach yields sufficient amino acid type and sequential information that the remaining links can be complemented with a uniformly labeled sample solely based on 3D HNCA and, if necessary, 3D HN(CO)CA spectra that are usually of good quality even under sensitivity limited conditions.…”
Section: Resultsmentioning
confidence: 99%